To perform the subtraction \( 4.66 \times 10^{-5} - 7.34 \times 10^{-7} \), we first need to express both numbers with the same exponent for easier calculations.
We can rewrite \( 4.66 \times 10^{-5} \) in terms of \( 10^{-7} \):
\[ 4.66 \times 10^{-5} = 4.66 \times 10^{-5} \times \frac{100}{100} = 466 \times 10^{-7} \]
Now, we can perform the subtraction:
\[ 466 \times 10^{-7} - 7.34 \times 10^{-7} = (466 - 7.34) \times 10^{-7} = 458.66 \times 10^{-7} \]
Now, we can convert \( 458.66 \times 10^{-7} \) back to standard scientific notation:
\[ 458.66 \times 10^{-7} = 4.5866 \times 10^{-5} \]
Thus, the result of the subtraction is:
\[ \boxed{4.5866 \times 10^{-5}} \]